Connecting short and long distance perspectives in freight transportation: Introduction to a special issue. (January 2023) - Guerrero, David; Niérat, Patrick; Thill, Jean-Claude
Abstract: Research on short and long distance freight transport artificially separates the segments of transport chains, which are interrelated and which might be better viewed as a continuum. The eight papers of this special issue aim to bridge this gap. The major disruptions in global supply chains of the last years brought to light the vulnerability of the transport system and the need for a more integrated approach for effective transport policies. This special issue explores some of the challenges facing freight transport in three research areas: supply chain studies, transport networks and warehouse location. It also identifies avenues for further research.